DETERMINASI KURS REFERENSI ACUAN TRANSAKSI VALUTA ASING/ JISDOR (JAKARTA INTERBANK SPOT DOLLAR RATE) PERIODE MEI 2013 – OKTOBER 2015 - Christina, Widya (Jurnal Ilmiah Mahasiswa FEB, 2016)
Unstable  exchange  rate  (IDR) was a  serious  problem that  must be intractable.  The movement of the exchange rate need to monitored periodically because the exchange rate is one of indicators which presented economic growth a country, therefore need to monitoring and research at regular intervals that regulator can make improvements monetary policy right on target so that reached stabilization of inflation and the exchange rate. This research using secondary data in the form of historical reference jisdor exchange rate, Inflation,  BI Rate, money of supply, exports and imports  from official  website  Bank  Indonesia  and  the  Ministry  of  Trade  of the Republic  of Indonesian. This reearch uses the method estimation regression analysis linear multiple with of runs data using Eviews 7.This study attempts to see if indicators macroeconomics (inflation and BI Rate) and indicators the financial sector (money supply, exports and imports ) worn in this research have an significant to determination of reference jisdor exchange rate. The results of research suggests that inflation, BI Rate, money supply, exports and imports significant to the movement of reference jisdor exchange rate. Results showing that money supply distributed is a most dominant can explain the movement of exchange rate reference jisdor.Key Words : Inflation, BI Rate, Money Supply (M1), Export, Imports, Reference Jisdor Exchange Rate.